Prevention and treatment of secretory diarrhea by the lysophosphatidic acid analog Rx100. Issue 13 (September 2018) - Thompson, Karin E; Ray, Ramesh M; Alli, Shanta; Ge, Wenbo; Boler, Alyssa; Shannon McCool, W; Meena, Avtar S; Shukla, Pradeep K; Rao, Radakrishna; Johnson, Leonard R; Miller, Mark A; Tigyi, Gabor J
Diarrheal disease is a severe global health problem. It is estimated that secretory diarrhea causes 2.5 million deaths annually among children under the age of five in the developing world. A critical barrier in treating diarrheal disease is lack of easy-to-use effective treatments. While antibiotics may shorten the length and severity of diarrhea, oral rehydration remains the primary approach in managing secretory diarrhea. Existing treatments mostly depend on reconstituting medicines with water that is often contaminated which can be an unresolved problem in the developing world. Standard treatments for secretory diarrhea also include drugs that decrease intestinal motility. This approach is less than ideal because in cases where infection is the cause, this can increase the incidence of bacterial translocation and the potential for sepsis. Our goal is to develop a safe, effective, easy-to-use, and inexpensive treatment to reduce fluid loss in secretory diarrhea. We have developed Rx100, which is a metabolically stable analog of lysophosphatidic acid. We tested the hypothesis that Rx100, similarly to lysophosphatidic acid, inhibits the activation of the cystic fibrosis transmembrane regulator Cl − channel and also reduces barrier permeability resulting in the decrease of fluid loss in multiple etiologies of secretory diarrhea. Here we have established the bioavailability and efficacy of Rx100 in cholera toxin-induced secretory diarrhea models. We have demonstrated the feasibility of Rx100 as an effective treatment for Citrobacter rodentium infection-induced secretory diarrhea. Using both the open- and closed-loop mouse models, we have optimized the dosing regimen and time line of delivery for Rx100 via oral and parenteral delivery. Impact statement: A critical barrier in treating diarrheal disease is easy-to-use effective treatments. Rx100 is a first in class, novel small molecule that has shown efficacy after both subcutaneous and oral administration in a mouse cholera-toxin- and Citrobacter rodentium infection-induced diarrhea models. Our findings indicate that Rx100 a metabolically stable analog of the lipid mediator lysophosphatidic acid blocks activation of CFTR-mediated secretion responsible for fluid discharge in secretory diarrhea. Rx100 represents a new treatment modality which does not directly block CFTR but attenuates its activation by bacterial toxins. Our results provide proof-of-principle that Rx100 can be developed for use as an effective oral or injectable easy-to-use drug for secretory diarrhea which could significantly improve care by eliminating the need for severely ill patients to regularly consume large quantities of oral rehydration therapies and offering options for pediatric patients.